LARVICIDAL ACTIVITIES OF EXTRACTS OF STEM BARK OF ANNONA RETICULATA AGAINST FILARIAL VECTOR CULEX QUINQUEFASCIATUS - SUBRATA MALLICK; GOUTAM CHANDRA (International Journal of Pharma and Bio Sciences, 2015)
Crude and three different solvent viz. Petroleum ether, hexane, and ethyl acetate extracts of stem bark of Annona reticulata Linn. (A. reticulata), (Family Annonaceae) were taken for observation for mosquito larvicidal activity. Mortality percentages, Log probit analyses, regression equations, and R2 values were determined for crude as well as different solvent extracts. Crude extract showed good larvicidal potency. LC50 values of Petroleum ether, hexane, and ethyl acetate extracts of stem bark of the plant were 15.2967, 14.0390, 1.0902 ppm respectively against 3rd instar larvae of Culex. quinquefasciatus Say, 1823 (Cx. quinquefasciatus) after 48 h of exposure. Ethyl acetate extract was applied again on 1st – 4th instars larvae of Cx. quinquefasciatus at different concentrations for larvicidal bioassay and was noticed 100% mortality with very low concentrations for all instars larvae. No mortality was noticed on control treatments. Qualitative phytochemical analyses revealed the presence of several secondary metabolites. No adverse effect was observed on non target organisms to ethyl acetate and crude extracts upto 72 h of post exposure.